Clinical Outcomes of Negative Balloon-Assisted Enteroscopy for Obscure Gastrointestinal Bleeding: A Systematic Review and Meta-Analysis - Shao, Xiao Dong; Shao, Hao Tian; Wang, Le; Zhang, Yong Guo; Tian, Ye (Frontiers in Medicine, 2022)
Background: For patients with obscure gastrointestinal bleeding (OGIB) finding the bleeding site is challenging. Balloon assisted enteroscopy (BAE) has become the preferred diagnostic modality for OGIB. The long-term outcome of patients with negative BAE remains undefined. The present study aimed to evaluate the long-term outcomes of patients with negative BAE results for OGIB and to clarify the effect of further investigations at the time of rebleeding with a systematic review and meta-analysis of available cohort studies. Methods: Studies were searched through the PubMed, EMBASE, and Cochrane library databases. The following indexes were analyzed: rebleeding rate after negative BAE, rebleeding rate after different follow-up period, proportion of patients undergoing further evaluation after rebleeding, percentage of patients with identified rebleeding sources, and percentage of patients with rebleeding sources in the small intestine. Heterogeneity was assessed using the I2 test. Results: Twelve studies involving a total of 407 patients were included in the analysis. The pooled rebleeding rate after negative BAE for OGIB was 29.1% (95% CI:17.2–42.6%). Heterogeneity was significant among the studies (I2 = 88%; P < 0.0001).Chi-squared test did not show difference in rebleeding rates between short and long follow-up period group (P=0.142).The pooled proportion of patients undergoing further evaluation after rebleeding was 86.1%. Among the patients who underwent further evaluation rebleeding sources were identified in 73.6% of patients and 68.8% of the identified rebleeding lesions were in the small intestine. Conclusion: A negative result of BAE in patient with OGIB indicates a subsequently low risk of rebleeding. Further evaluation should be considered after rebleeding.